South American medicinal plants for the symptomatic treatment of benign prostatic hyperplasia: A systematic review - Eliana Solorzano; Paolo Pastore; Davide Grisafi (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: Benign prostatic hyperplasia (BPH) is one of the prevalent age-related medical conditionin men. In the last 20 years, alternative therapies, especially those based on herbs, are increasingly preferred. The most popularly consumed herb is Serenoa repens, a plant growing in the subtropical south-eastern United States which has shown very efficient results compared to pharmacological conventional treatments both in terms of cost and risks associated with them. Nevertheless, the same trial found no difference between S. repens and placebo according to the American Urological Association Symptom Score Index. As more and more consumers are turning increasingly towards natural therapies, it would be appropriate to promote the recognition of the value of other medicinal plants with potential applicability through comprehensive research. For this purpose, a descriptive comparison between several South-American plants little publicised in the pharmaceutical market is presented to slightly narrow the gap between the reliable evidence-based and popular information for consumers and the pharmaceutical industry. Experimental: With this approach, a review of the literature was conducted through an electronic consultation of two databases, Science Direct and Google Scholar™. Results: This narrative review highlights the wide range of natural medicines available for controlling the inflammatory symptoms of the lower urinary tract, which could be more explored from a pharmacological and chemical point of view. Recommended applications/industries: The future use of natural products requires further investment in pre-clinical research and in clinical trials that investigate stability and a profitable pharmacokinetic/pharmacodynamic ratio. Although they are well tolerated and used daily by South American populations, the industry's proper commercial focus on these natural remedies cannot be separated from appropriate phyto-vigilance actions promoted